Insulin Resistance in Obese Women: Does it Affect Fertility? Resistensi Insulin pada Perempuan Obesitas: Apakah Mempengaruhi Kesuburan? - Satrio B. Purnomo; Bobby I. Utama; Yusrawati; Ori John; Muhammad Iqbal (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: To know the correlation of insulin resistance with body mass index in obesity women infertility.Method: This research used a cross-sectional study design. This study was conducted on February 2017 until January 2019 at Obstetric and Gynecology Division of RSUP Dr. M. Djamil and Ibnu Sina Hospital in Padang. The population of the study were all patients were obese in women of reproductive age with infertility complaints with a total sample of 27 people. The sampling technique was consecutive sampling. Data analysis was done by univariate and bivariate using Pearson correlation test.Results: We found that less than half of the respondents experienced insulin resistance with HOMA-IR values > 2,5 (22.2%) and more than half of respondents did not experience insulin resistance with HOMA-IR values < 2,5 (77.8%). There was a correlation of insulin resistance with body mass index in obese female infertility (p<0,05) with strong relationship strength. Conclusions: There was a correlation of insulin resistance with body mass index in obese female infertility.Keywords: infertility, insulin resistance, obesity Abstrak Tujuan: Mengetahui korelasi resistensi insulin dengan indeks massa tubuh pada infertilitas perempuan obesitas.Metode: Penelitian ini menggunakan desain potong lintang. Penelitian dilakukan di Poliklinik Bagian Obstetri dan Ginekologi RSUP Dr. M. Djamil Padang dan RS Islam Ibnu Sina Padang sejak bulan Februari 2017 – Januari 2019. Populasi pada penelitian ini adalah semua pasien yang mengalami obesitas pada perempuan usia reproduksi dengan keluhan infertilitas dengan jumlah sampel sebanyak 27 orang. Teknik pengambilan sampel dengan consecutive sampling. Analisis data dilakukan secara univariat dan bivariat dengan menggunakan uji korelasi pearson. Hasil: Hasil penelitian diketahui kurang dari separuh responden mengalami resistensi insulin dengan nilai HOMA-IR > 2,5 (22,2%) dan lebih dari separuh responden tidak mengalami resistensi insulin dengan nilai HOMA-IR < 2,5 (77,8%). Terdapat korelasi resistensi insulin dengan indeks massa tubuh pada infertilitas perempuan obesitas (p<0,05) dengan kekuatan hubungan kuat.Kesimpulan: Terdapat korelasi resistensi insulin dengan indeks massa tubuh pada infertilitas perempuan obesitas.Kata kunci: infertilitas, obesitas, resistensi Insulin.